Romidepsin Enhances the Killing Ability of NKG2D-CAR-T Cells through Enhanced Expression of NKG2DL against Ovarian Cancer Cells - Liang Wang; Xite Lin; Lirui Yu; Pengming Sun (Clinical and Experimental Obstetrics & Gynecology)
Background: Upregulating tumor cell targeting antigens and improving the cytotoxicity of chimeric antigen receptor T cell (CAR-T) are expected to facilitate better treatment efficacy for solid cancers represented by ovarian cancer. Methods: Killer cell lectin-like receptor subfamily K member 1 ligands (NKG2DL) are the target antigens for ovarian cancer. NKG2D-CAR-T cells were constructed for NKG2D ligand on the ovarian cancer cell surface. We used flow cytometry to evaluate the expression of NKG2DL on SKOV3 (a human ovarian cancer adenocarcinoma cell line). Innovatively, when combined with romidepsin to treat ovarian cancer cell SKOV3, to evaluate the killing ability of the combined strategy, we verified the cytotoxicity of CAR-T cells by lactate dehydrogenase (LDH) release test and determined the secretion of cytokines by enzyme-linked immuno sorbent assay (ELISA). Results: The results of flow cytometry showed effective activation of the NKG2D-CAR-T cells, and romidepsin treatment resulted in increased expression of NKG2DL on the surface of SKOV3. Cytotoxicity test showed that romidepsin could enhance the killing ability of NKG2D-CAR-T cells against ovarian cancer cells by regulating their NKG2DL expression (p < 0.05). The killing effects and secretion of interferon-γ (IFN-γ) increased synchronously (p < 0.05). Levels of interleukin-2 (IL-2) and Pore-forming protein (PFP) were statistically significant at a low target ratio but programmed cell death protein 1 (PD-1) remained unaffected (p ≥ 0.05). Conclusions: Enhancing the expression of tumor target antigen is a solution to improve the limited application of CAR-T cells in solid cancers.